ANALISIS NILAI KARAKTER YANG TERKANDUNG PADA CERITA ANAK BERJENIS FABEL PADA BUKU SISWA KELAS 2 TEMA 7 SD/MI REVISI 2017 - Muchammad Khilmi; Ika Ratih Sulistiani; Mutiara Sari Dewi (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
Education is a necessity and the most important aspect in life, especially in the current era of globalization. education that is important right now is character education, inculcation of character values can be done in various ways. one of them is through fables in student books Character education is needed because the reality of national issues that are developing at this time, for example, has not been to live up to and practice the values of Pancasila, the shifting of ethical values in national and state life, and the threat of national disintegration. The purpose of this study was to find out and analyze what character values contained in the fable-type children's stories in theme book 7 grade 2 SD / MI revised 2017. This study used a qualitative research approach with the type of content analysis research. the results of this study can be concluded that there are values of the character of peace, creative, cooperation, discipline, hard work, curiosity, social care and responsibility. Keywords: Analysis, Character values, Fables, children's stories. SD / MI